Os videogames como recursos de ensino-aprendizagem: uma experiência nas aulas de matemática do ensino fundamental da rede pública - Burihan, Cláudia Maria Lopes de Avelar (2009)
With the new technologies new forms of languages emerged and consequently, new culture forms. Videogames, inserted in this context appears as a hero for young people and teenagers and villainous for parents and educators. In the center of this subject it is school, with a double challenge: to stay as a knowledge construction space and at the same time, educate for changes. In this context, it was developed the present document, with the objective of investigating the use of videogames in the education context. Starting from an elaboration of a pedagogic project in the mathematics discipline entitled The Sims's Logic , it was used as object study the simulation game The Sims 2 . The research aimed to analyze the possibilities of use of videogames as teaching-learning strategy. Starting from a contextual analysis, a panoramic vision of the education public politics in Brazil was aimed and also the existing proposals regarding the area of Education Technology. The game concept was introduced starting from languages games and later as a culture form proposed by Huizinga. After a historical briefing about the videogames and their use in education in a constructivism conception by Piaget (1978;1983;1990;2003) and Vigotysky ( 1994; 2005)and was made a pedagogic analysis of some games using as pedagogic reference Coll ( 1999 ) and Zabala ( 1998). The methodological strategies used in the research involved five stages: application of the initial questionnaire (diagnosis); elaboration of the project; in locus development ; application of the final questionnaire and analysis of the data. As a result, it was verified that the videogames are not created with education objectives, but they can be used with such purpose since associated to a pedagogic project that establishes strategies that allows one to work the contents in different dimensions, either, conceptual, procedure or attitude wise